1986
DOI: 10.1346/ccmn.1986.0340310
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Diffusion of Eu And Th in Deep-Sea Sediments: Experimental Results and a Numerical Model

Abstract: Experimentally, the sorption of Eu onto clay-rich sediments was very rapid in the first few seconds and slowed over an interval of minutes to hours. Rate curves were similar in shape to those of a-iron hydroxide, rather than of the oxalate-extracted residual sediment, indicating the importance of oxyhydroxide-like phases in the uptake of Eu onto red-clay sediments. For day-rich sediments, numerical modeling reproduced the general features of a series of diffusion experiments. To a first approximation, the pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Direct experimental evidence linking particle aggregation and metal behavior is needed to distinguish sorption control by coagulation reactions from control by diffusion of the sorbate through surface films or pore spaces (e.g., Enfield et al. 1976;Epstein, 1983;Wu and Gschwend, 1986) or, in the case of radionuclidcs, from slow isotopic exchange (e.g., Johnston, 1977).…”
Section: The Brownian-pumping Model: Criticisms and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct experimental evidence linking particle aggregation and metal behavior is needed to distinguish sorption control by coagulation reactions from control by diffusion of the sorbate through surface films or pore spaces (e.g., Enfield et al. 1976;Epstein, 1983;Wu and Gschwend, 1986) or, in the case of radionuclidcs, from slow isotopic exchange (e.g., Johnston, 1977).…”
Section: The Brownian-pumping Model: Criticisms and Implicationsmentioning
confidence: 99%
“…Nash and Choppin (1980) estimated that in natural waters at 0.1 mg 1-1 DOC (humate = 4 x 10-7 eq 1-1) the ratio of [ThHu]/ [Thdiss] would be about 4 x 10 10 . Sequential filtration and ultrafiltration experiments by Santschi et al (\987;1983) have shown that radioisotopes of particle reactive elements are involved in dynamic cycles of aggregation and disaggregation of colloids in the water column of coastal marine ecosystems while Buchholtz et al (1986) demonstrated the aggregation of colloidal radionuclides in laboratory batch experiments using marine sediments. [47,4 b.…”
Section: Introductionmentioning
confidence: 99%